2023
DOI: 10.1111/rda.14468
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTNR1A and GDF9 gene allelles with the reproductive performance, response to oestrus induction treatments and prolificacy, in improved and non‐improved local indigenous sheep breeds

Danai Antonopoulou,
Ioannis A. Giantsis,
George K. Symeon
et al.

Abstract: Sheep farming plays a crucial role for Mediterranean countries, wherefrom a plethora of dairy products is produced. Yet, numerous indigenous sheep breeds in temperate latitudes such as the Mediterranean present a serious drawback that milk production is impaired by the seasonality of reproduction. Towards the efforts for reduction of this phenomenon, the purpose of this study was to evaluate and compare different oestrus synchronization treatments, as well as to associate two genes alleles', namely the MTNR1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this study, two polymorphic sites were shown and detected using MnlI and RsaI enzyme digestion [23]. Following this discovery, different studies in sheep have been conducted to investigate the existence of any relationship between MTNR1A gene polymorphism and variation in reproductive performance [25][26][27][28][29][30][31][32][33][34][35]. Specifically, different investigations have shown the presence of a polymorphic cleavage site in the g.17355452 (G > A) position, evidenced by the MnlI enzyme, and in the g.17355458 (C > T) position, evidenced by the RsaI enzyme [36,37].…”
Section: Introductionmentioning
confidence: 96%
“…In this study, two polymorphic sites were shown and detected using MnlI and RsaI enzyme digestion [23]. Following this discovery, different studies in sheep have been conducted to investigate the existence of any relationship between MTNR1A gene polymorphism and variation in reproductive performance [25][26][27][28][29][30][31][32][33][34][35]. Specifically, different investigations have shown the presence of a polymorphic cleavage site in the g.17355452 (G > A) position, evidenced by the MnlI enzyme, and in the g.17355458 (C > T) position, evidenced by the RsaI enzyme [36,37].…”
Section: Introductionmentioning
confidence: 96%